Sistemas agrícolas e sistema de indicadores: avaliação do impacto das alterações climáticas sobre a segurança alimentar numa bacia de inundação da Amazônia - Marie Flore Doyen; Anne Elisabeth Laques; Helen Gurgel; Lucas Garcia (Confins)
In Amazonia, climate change mainly involves discorder of the floods. It disturbs the agricultural systems of the waterside population of the Amazon and exposes those populations to food insecurity. In order to facilitate the analysis of the study area farming systems (Lago Grande de Curuaï), a typology was made using Bertin’s matrix, allowing the identification of four typical systems: agri-forestry, agricultural, agro-pastoral and fish-pastoral. A system of indicators was made following the « Principle, Criteria, Indicators » method, using the information on the agricultural systems and the two pillars of food security (availability and access) as a main base for analysis. One principle, three criteria and seven indicators estimated food security on the scale of the typical agricultural systems depending of two scenarios: with and without the emergence of extreme events. A degradation of food security is observed with the emergence of extreme events, and the agro-pastoral system is the most affected by these crisis.